QUBIC III: Laboratory characterization - Torchinsky, S. A.; Hamilton, J. C.; Piat, M.; Battistelli, E. S.; Chapron, C.; D'Alessandro, G.; De Bernardis, P.; De Petris, M.; Gamboa Lerena, Martín Miguel; González, M.; Almela, Daniel Alejandro; Arnaldi, Luis Horacio; et al. (IOP Publishing, 2022)
Fil: Torchinsky, S. A.. Universite de Paris; Francia. Centre National de la Recherche Scientifique. Observatoire de Paris; Francia